2023
DOI: 10.1002/cptc.202300072
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Photocatalytic Properties of the CsV0.625Te1.375O6 Mixed‐Valence β‐Pyrochlore Compound

Abstract: A new β‐pyrochlore compound with complex composition of Cs(V3+0.0625V5+0.5625Te4+0.34375Te6+1.03125)O6 has been synthesized by a solid‐state reaction and characterized by single‐crystal X‐ray diffraction and thermal analysis. The compound possesses the typical cubic symmetry with space group , however some of the oxygen atoms shift from the special position 48 f to the general crystallographic positions 32e, 96 g and 96 h. This shift is caused by complex B‐site composition with mixed‐valence vanadium and tell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In TiO 2 , when N element doping and different V o valence states coexist, the structure changes and the middle of gravity of charges deviates, resulting in electrostatic interactions between atoms and generating a local electric field and an electric dipole moment, which changes the carrier activity. In accordance with the Debye equation, 48 the electric dipole moment is = nqR (6) where n stands for the electron number; q represents the amount of charge; and R indicates the distance about charges. Lattice deformation occurred in the 2D ) systems, resulting in electric dipole moments.…”
Section: Acs Sustainablementioning
confidence: 99%
See 1 more Smart Citation
“…In TiO 2 , when N element doping and different V o valence states coexist, the structure changes and the middle of gravity of charges deviates, resulting in electrostatic interactions between atoms and generating a local electric field and an electric dipole moment, which changes the carrier activity. In accordance with the Debye equation, 48 the electric dipole moment is = nqR (6) where n stands for the electron number; q represents the amount of charge; and R indicates the distance about charges. Lattice deformation occurred in the 2D ) systems, resulting in electric dipole moments.…”
Section: Acs Sustainablementioning
confidence: 99%
“…Their results showed that Mn valence states considerably influence the SCR activity of the MnO x /TiO 2 surface, and Mn 4+ is essential for low-temperature SCR activity. Fukina 6 studied the photocatalytic ability of CsV 0.625 Te 1.375 O 6 materials containing valence states V 3+ , V 5+ , Te 4+ , and Te 6+ via the solidphase reaction method. They discovered that the photocatalytic ability improves when the Te 4+ ion content increases.…”
Section: ■ Introductionmentioning
confidence: 99%